Пленница: [роман] / Татьяна Устинова, Павел Астахов - Устинова Татьяна Витальевна (Дела судебные, 2023)
Экземпляры: ф.7 (2024) / Инвентарный номер: 60085 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: У 80 / ББК: 84(2=411.2)6-445.7